The Stabilization of Postoperative Exo-drift in Intermittent Exotropia after Surgical Treatment - Park, Hoon (Korean J Ophthalmol, 2016)
PURPOSE: To investigate the long-term clinical course of intermittent exotropia after surgical treatment to determine whether and when postoperative exo-drift stabilizes, and the required postsurgery follow-up duration in cases of intermittent exotropia. METHODS: We retrospectively reviewed the medical records of patients diagnosed with intermittent exotropia who underwent surgical treatment between January 1992 and January 2006 at Yeungnam University Hospital and postoperatively performed regular follow-up examinations for up to 7 years. We also analyzed the difference in exo-drift stabilization, according to surgical procedure. RESULTS: A total of 101 patients were enrolled in the study. Thirty-one patients underwent lateral rectus recession and medial rectus resection (R&R) and 70 patients underwent bilateral lateral rectus recession (BLR). The postoperative angles of deviation increased significantly during the initial 36 months, but no subsequent significant changes were observed for up to 84 months. Follow-ups for 7 years revealed that more than 50% of the total amount of exo-drift was observed within the first postoperative year. In addition, the angles of deviation at 1 year correlated with those at 7 years postoperatively (Pearson correlation coefficient r = 0.517, p < 0.001). No significant exo-drift was observed after 36 months in patients who underwent BLR, whereas after 18 months in patients who underwent R&R. CONCLUSIONS: The minimum postoperative follow-up required after surgical treatment to ensure stable results is 36 months. In particular, careful follow-up is necessary during the first postoperative year to detect rapid exo-drift. Patients who underwent BLR required a longer follow-up than those who underwent R&R to ensure stable postoperative alignment.